Should we Bend towards Blending? How? (Journal of NELTA, 2018)
Blended learning that combines face-to-face and online educational delivery can occur at activity, course, program, and institution level. In this study, course-level blending in Critical Discourse Analysis (CDA) course was examined. The students of face-to-face mode were enrolled in Moodle. However, their participation in Moodle was optional (i.e. low level of blending). Data collected from a class test and end-of-semester questionnaire survey suggest that blending does have a positive effect on learning achievement and students do perceive blending positively. Overall, the study shows optimism towards the prospects of blended learning. However, for the successful integration of Moodle, easy access to the Internet and orientation for using Moodle are to be ensured.Journal of NELTA ,  Vol. 22, No. 1-2, 2017 December, page: 54-67